Biochirality : origins, evolution and molecular recognition - Cintas, Pedro (Topics in Current Chemistry, 2013)
Early History of the Recognition of Molecular Biochirality, by Joseph Gal, Pedro Cintas Synthesis and Chirality of Amino Acids Under Interstellar Conditions, by Chaitanya Giri, Fred Goesmann, Cornelia Meinert, Amanda C. Evans, Uwe J. Meierhenrich Chemical and Physical Models for the Emergence of Biological Homochirality, by son E. Hein, Dragos Gherase, Donna G. Blackmond Biomolecules at Interfaces: Chiral, Naturally, by Arántzazu González-Campo and David B. Amabilino  Stochastic Mirror Symmetry Breaking: Theoretical Models and Simulation of Experiments, by Celia Blanco, David Hochberg Self-Assembly of Dendritic Dipeptides as a Model of Chiral Selection in Primitive Biological Systems, by Brad M. Rosen, Cécile Roche, Virgil Percec Chirality and Protein Biosynthesis, by Sindrila Dutta Banik, Nilashis Nandi